Thermal and near-infrared light induced spin crossover in a mononuclear iron(ii) complex with a tetrathiafulvalene-fused dipyridophenazine ligand. Issue 28 (30th June 2016) - Pointillart, F.; Liu, X.; Kepenekian, M.; Le Guennic, B.; Golhen, S.; Dorcet, V.; Roisnel, T.; Cador, O.; You, Z.; Hauser, J.; Decurtins, S.; Ouahab, L.; et al.
Abstract : A thermal and photo-induced spin transition in a tetrathiafulvalene-based Fe(ii ) complex. Abstract : A mononuclear Fe(ii ) complex involving a tetrathiafulvalene-based ligand exhibits thermal spin-crossover (around 143 K) with pronounced hysteresis behaviour (48 K). The chromophoric and π-extended ligand allows Near-Infrared (NIR) sensitization for the light-induced excited spin-state trapping (LIESST) with T (LIESST) = 90 K.